The role of avian seed dispersal in forest regeneration on degraded areas of a sub-humid forest in Guinea-Bissau (West Africa) - Gomes, Sara Isabel da Costa (2019)
Tese de mestrado, Biologia da Conservação, Universidade de Lisboa, Faculdade de Ciências, 2019